Influence of optical Airy transform on non-diffracting propagation distance of finite energy Airy beams - Chu, Xingchun; Liu, Rongjiang; Wang, Xiang; Han, Zhongxiang; Ni, Yanhui (Oficyna Wydawnicza Politechniki Wrocławskiej, 2021)
Finite energy Airy beams (FEAB) generated in laboratory have a short non-diffracting propagation distance (NDPD), which restricts its application in laser communication, laser detection and other fields. Effects of optical Airy transform (OAT) on NDPD of FEAB is analyzed. By comparing the theoretical formulas of the FEAB before and after the OAT, we find that when the transform parameter α of the OAT is larger than zero, the transverse scaling factor of the transformed FEAB is greater than that before the transformation, while the transformed exponential decay factor is smaller than that before the transformation. Using the Huygens–Fresnel diffractive integral, we derive the propagation formula of the transformed FEAB. Initial intensity distribution of FEAB before and after the OAT is compared. Propagation dynamics of the transformed FEAB with different α is numerically simulated and its NDPD is quantitatively evaluated. Results show that: with the increase of α, side lobes of the transformed FEAB increase, its main lobe and side lobes become wider than that before the transformation, and the inclination of the propagation trajectory decreases. When α is greater than half of the transverse scaling factor, the NDPD of the transformed FEAB increases rapidly.
Optica Applicata, Vol. 51, 2021, nr 4, s. 473-482
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; physics optics; non-diffracting beam; finite energy Airy beams; non-diffracting propagation distance; optical Airy transform